(untitled) (TAJ: Journal of Teachers Association, 2010)
Use of local fasciocutaneous flap is gaining popularity as an effective method of treating type III B open tibial shaft fracture in adults. We treated 16 fractures at National Institute of Traumatology and Orthopedic Rehabilitation, Dhaka during the period between March 1993 and December 1994 to evaluate the result of management of type III B open tibial shaft fracture using local fasciocutaneous flaps in adults. Of the 16 tibial fractures the mean healing time was 6.13 months (3.5 to 11 months). The major post operative complications were deep infections (43.75%), non-union (31.25%) and malunion (12.5%). The results were excellent in 18.75%, good in 37.5%, fair in 18.75% and poor in 25% cases. Salvage of the limb should be the primary aim of management of type III B open tibial shaft fracture. We conclude that use of local fasciocutaneous flap is an easy and effective method of management of open type III B tibial shaft fractures. DOI: 10.3329/taj.v22i1.5033 TAJ 2009; 22(1): 119-122